2017
DOI: 10.22606/afse.2017.12004
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Modeling of Prickly Pear Juice Clarification

Abstract: Abstract. Raw juice of prickly pear is viscous and turbid in nature. The clarity of such juice can be improved through enzymatic clarification. An experiment was conducted to standardize the process parameters for clarification of prickly pear juice using pectinase enzyme. Experiment was designed according to response surface methodology (RSM) by keeping three selected independnt variables at five different levels, i.e. enzyme concentrations (0.01, 0.026, 0.050, 0.074 and 0.09%), incubation temperatures (40, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Prickly pear fruit pulp was extracted adopting the method of Davara et al (2017) with slight modifications indicated in Fig 1 . Milk was fermented (Robinson and Tamime, 1975) Formulation, Characterization and Storage Stability of Prickly Pear (Opuntia ficus) Fruit and Milk Based Fermented Beverage and PPFMB was prepared according to manner described in Fig 1 . Based on review of literature and preliminary trials levels of milk fat and prickly pear fruit pulp were decided and selected as factors for the development of fermented beverage and presented in Table 1.…”
Section: Preparation Of Prickly Pear Fruit and Milk Based Fermented B...mentioning
confidence: 99%
“…Prickly pear fruit pulp was extracted adopting the method of Davara et al (2017) with slight modifications indicated in Fig 1 . Milk was fermented (Robinson and Tamime, 1975) Formulation, Characterization and Storage Stability of Prickly Pear (Opuntia ficus) Fruit and Milk Based Fermented Beverage and PPFMB was prepared according to manner described in Fig 1 . Based on review of literature and preliminary trials levels of milk fat and prickly pear fruit pulp were decided and selected as factors for the development of fermented beverage and presented in Table 1.…”
Section: Preparation Of Prickly Pear Fruit and Milk Based Fermented B...mentioning
confidence: 99%
“…This releases the fruit juice and increases yield (Demir et al, 2001;Saxena et al, 2014). (Enzymatic treatments using pectinase have also assisted in the improvement of yield and reduction of turbidity of prickly pear juice (Davara et al, 2017). The fundamental physical property of food products is color.…”
Section: Introductionmentioning
confidence: 99%